2022
DOI: 10.1093/dote/doac031
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of neoadjuvant treatment with immune checkpoint inhibitors in esophageal cancer: real-world multicenter retrospective study in China

Abstract: Summary Immune checkpoint inhibitors (ICIs) have shown a powerful benefit in the neoadjuvant therapy for esophageal cancer, but evidence for its safety and efficacy is limited and may not reflect real-world practice. We retrospectively reviewed the database of treatment-naive patients from 15 esophageal cancer centers in China who received ICIs as neoadjuvant treatment for locally advanced esophageal cancer from May 2019 to December 2020. The primary endpoints were rate and severity of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
6
9
1
Order By: Relevance
“…A recently published real-world multicenter retrospective study in China which mainly included patients with locally advanced ESCC reported a pCR rate of 42.3% and 25.5% after neoadjuvant immunochemoradiotherapy and immunochemotherapy, respectively, which was approximative to the prospective outcomes in this study (12). In standard NCRT, the addition of radiotherapy to chemotherapy could significantly promote tumor shrinkage (33).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…A recently published real-world multicenter retrospective study in China which mainly included patients with locally advanced ESCC reported a pCR rate of 42.3% and 25.5% after neoadjuvant immunochemoradiotherapy and immunochemotherapy, respectively, which was approximative to the prospective outcomes in this study (12). In standard NCRT, the addition of radiotherapy to chemotherapy could significantly promote tumor shrinkage (33).…”
Section: Discussionsupporting
confidence: 58%
“…For safety, it should be cautious that the addition of ICIs to NCRT could increase the risk of severe even lethal complications. Compared with this pooled analysis of trials, grade 3-4 AEs were less frequently reported in the real-world practice, with 23.3% and 12.7% in neoadjuvant immunochemoradiotherapy and immunochemotherapy, respectively (12). The disagreements on safety evaluation may resulted from the different nature of two studies, and we tended to hold the opinion that severe AEs were underestimated in real-world data possibly due to non-standardized medical records and potential selective preference to patients with good performance or few comorbidities.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Zhu et al reported that neoadjuvant immunochemoradiotherapy could not improve the pCR rate than neoadjuvant chemoradiotherapy (nCRT) for ESCC, but significantly increased the risk of severe adverse events (8). Another multicenter retrospective study that included 370 ESCC patients showed that the pCR rates of mono-immunotherapy, nCIT, and nCRT plus immunotherapy were 12.1%, 25.5%, and 42.3%, respectively (9). Hence, neoadjuvant PD-1/PD-L1 inhibitors in combination with chemotherapy or chemoradiotherapy are becoming a new therapeutic frontier for resectable ESCC with promising clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%